2015
DOI: 10.1016/j.infbeh.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Feature or location? Infants and adults adopt different strategies to search for a hidden toy in an ambiguous task

Abstract: 15 16Evidence suggests that infants and adults attribute different importance to certain object 17 properties when performing object-directed actions. Namely, infants tend to rely on 18 information about an object's location, whereas adults are more likely to base their actions on 19 its features. In this study, we tested whether the strategic choices of infants (aged 13 months) 20 and adults would be modified by the context of the demonstration. Participants watched as an 21 experimenter hid a ball under one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We show that in a social context with eye contact, 9-month-old infants preferentially processed an object’s identity but not its location, clarifying that eye contact shaped the infants’ representations of novel objects. Regarding the object’s location and identity processing, previous research with infants under 1 year of age has shown that since they might have difficulty integrating the two processes with object representations, they tend to rely on information about an object’s location rather than its identity [ 25 , 26 ]. Nevertheless, the 9-month-olds in our study processed object identity in a social context with eye contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that in a social context with eye contact, 9-month-old infants preferentially processed an object’s identity but not its location, clarifying that eye contact shaped the infants’ representations of novel objects. Regarding the object’s location and identity processing, previous research with infants under 1 year of age has shown that since they might have difficulty integrating the two processes with object representations, they tend to rely on information about an object’s location rather than its identity [ 25 , 26 ]. Nevertheless, the 9-month-olds in our study processed object identity in a social context with eye contact.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that spatiotemporal location has primacy over identifying features when infants process information about objects (e.g., [ 22 24 ]). Especially for infants under 1 year of age, since they might have difficulty integrating the two processes with object representations, they tend to rely on information about an object’s location rather than its identity [ 25 , 26 ]. After 1 year of age, they can use featural information to individuate objects [ 27 , 28 ], manifesting functional integration between object identity and object localization processing.…”
Section: Introductionmentioning
confidence: 99%
“…When 22‐month‐old children observed that an object was hidden beneath one of four containers that were placed in a rectangle around them in the room, and children were thereafter rotated with covered eyes, they benefitted in their search when containers were visually discriminable (i.e., different colors and different stickers) as well, and found the objects more often than children in the control condition with identical containers (Garrad‐Cole, Lew, Bremner, & Whitaker, ). Nevertheless, young infants appear to use less object features in their spatial search than older children or adults and rely instead more strongly on spatial cues, such as the initial location of the hidden object (Haun et al., ; Oláh, Kupán, Csík, Király, & Topál, ).…”
mentioning
confidence: 99%